Use of a real-time continuous glucose monitor in healthy dogs during anesthesia - Bilicki, Kerry (Kansas State University, 2009)
The use of continuous blood glucose monitors (CBGMs) has recently come into favor in human medicine for the control and monitoring of the diabetic patient. It allows for a higher degree of accuracy of the true glucose curve throughout a 72-hour period. With this information, physicians are better equipped to treat and manage diabetic patients. Recently, this modality has been verified for use in veterinary patients including cats and dogs. This is an excellent source of information, especially in the management of difficult to regulate veterinary patients. This device has potential for use in various applications, particularly for the monitoring of patients with various diseases under general anesthesia. In order to ensure accurate results do occur when an animal is under general anesthesia, the continuous blood glucose monitor was evaluated on apparently healthy patients under anesthesia for routine procedures such as ovariohysterectomies and orchiectomies. In this manner, the monitor was tested on anesthetized patients that had the potential to experience hypothermia, hypotension, and other anesthesia-associated complications that can be typical of patients that could benefit from the CGMS.
Keywords: Glucose; Monitor; Anesthesia; Dogs; Continuous; Biology, Veterinary Science (0778)